Border Securitization In Globalization Era Concept Renewal In Context Of Comprehensive Holistic Multi-Modal Approach (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract:This Study Focuses On Border Securitization Highlighting The Effective Role Of Some Mediators Such As Political Border Security Variable, Which Is Of Great Importance In Light Of Classical Security Approaches Failure, That Are Drought And Insufficient In Securing States Political Borders, Adding To The Role Increasing Of Some Societal Actors From Modern Perspective. Research Is Based On The Descriptive, Analytical Approach, Using Historical Survey To Clarify The Rupture Between Classical And Modern Perspective, Where Results Prove The Necessity To Shift Away From Classical Vision Through Comprehensive Approach In Order To Realize Border Protection As A Part Of Development Goals, Considering The Growth, Overlap Of Local, Regional And International Factors In Response To The Manifestations Of Global Thought That Has Become Nourishing Most Of Contemporary Concepts. Keywords: Borders, Border Securitization, Globalization & Global Though, Comprehensive Holistic Multi-Modal Approach, Human Security.